2010
DOI: 10.1186/1476-4598-9-231
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty1, a new target of the angiostatic agent 16K prolactin, negatively regulates angiogenesis

Abstract: BackgroundDisorganized angiogenesis is associated with several pathologies, including cancer. The identification of new genes that control tumor neovascularization can provide novel insights for future anti-cancer therapies. Sprouty1 (SPRY1), an inhibitor of the MAPK pathway, might be one of these new genes. We identified SPRY1 by comparing the transcriptomes of untreated endothelial cells with those of endothelial cells treated by the angiostatic agent 16 K prolactin (16 K hPRL). In the present study, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…It is also important to emphasize that several recent studies have implicated the potential role of miRNAs and Spry1 as regulators of extracellular matrix proteins. For instance, miR-377 was shown to play a pivotal role in increased fibronectin protein production in mesangial cells (8), and a recent report by Sabatel et al (70) provided evidence that Spry1 may serve as an endogenous angiogenesis inhibitor, whose silencing can modulate the interaction between cells and extracellular matrix proteins. Interestingly, although the role of Spry1 on fibronectin synthesis has recently been described (70), the effect of Spry1 on cell apoptosis is less understood with a number of published studies suggesting that Spry1 can increase or decrease apoptosis at the cellular level, depending on the cellular context (12,67,71,72).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to emphasize that several recent studies have implicated the potential role of miRNAs and Spry1 as regulators of extracellular matrix proteins. For instance, miR-377 was shown to play a pivotal role in increased fibronectin protein production in mesangial cells (8), and a recent report by Sabatel et al (70) provided evidence that Spry1 may serve as an endogenous angiogenesis inhibitor, whose silencing can modulate the interaction between cells and extracellular matrix proteins. Interestingly, although the role of Spry1 on fibronectin synthesis has recently been described (70), the effect of Spry1 on cell apoptosis is less understood with a number of published studies suggesting that Spry1 can increase or decrease apoptosis at the cellular level, depending on the cellular context (12,67,71,72).…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation is already documented in response to 16 K prolactin, where a strong increase at RNA level is hardly pronounced at the protein level. 22 Although mitogen-induced signaling as well as expression of oncogenic Ras isoforms had no influence on Spry1 levels in serumstarved cells, tumor cells harboring a mutated version of K-Ras express on average more Spry1 protein. In agreement with our observation, it was shown that in tumorderived cells, increased Spry1 expressions are accompanied by higher levels of phosphorylated ERK1 and 2 (pERK1/2).…”
Section: Discussionmentioning
confidence: 99%
“…After transfection for 24 h, cells were washed and kept for additional 48 h in serum-free medium. Functional assays were performed as previously described below and in [34,35].…”
Section: Transfection Of Pre-mir-205 In Huvecmentioning
confidence: 99%